(3GdQhVI GdRGgQI GdfGaYI aj GdOfjG hGdBNQIs - (3eMeO Hf SdjeGf Hf SYO Hf eSYhO GdcGajLj GdQhej GdMfaj, eMjj GdOjf, CHh YHO Gddg, J (B879 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdEfSGf hYdeg CeG HYO abO CTGQ Ydi ef Cf CLeY dg CbhGd GdYdeGA ai GdLeYI heG jJYdb HgG s
(3BNQgG (B:s
(3ajSCd Gddg JYGdi TjFkG EdG CYWGg EjGg SFd HYV GdeTGjN Yf djdI GdLeYI dCf aVjdI gPg GddjdI dUdGI GdLeYI hCfgG ai Gdjhe acGf Gdjhe CaVd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B6s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(115) s
Keywords: (3GdeLGejYs